2022
DOI: 10.1161/strokeaha.121.036635
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms After Stroke: The Effects of Anatomy and Coping Style

Abstract: Background: Posttraumatic stress disorder (PTSD) can be triggered by life-threatening medical emergencies, such as stroke. Data suggest that up to 25% of stroke survivors will develop PTSD symptomatology, but little is known about predisposing factors. We sought to examine whether neuroimaging measures and coping styles are related to PTSD symptoms after stroke. Methods: Participants were survivors of first-ever, mild-moderate ischemic stroke, or transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…On the other hand, the presence of maladaptive coping styles has already been shown to be a predictor for PTSD severity three months after the TIA [ 47 ]. In a recent study, Assayag et al (2022) similarly examined risk factors for the development of PTSD after stroke and found that high-anxious and defensive coping styles were associated with a six-fold higher risk for poststroke PTSD in comparison with low-anxious and repressive coping styles [ 48 ]. However, in the context of our finding that TIA patients reported an avoidance coping style, it must be considered that the phenomenon of avoiding feelings or thoughts can also be regarded as a cardinal symptom of PTSD, which indeed was demonstrated in 24.6% of the cases in the population we studied [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of maladaptive coping styles has already been shown to be a predictor for PTSD severity three months after the TIA [ 47 ]. In a recent study, Assayag et al (2022) similarly examined risk factors for the development of PTSD after stroke and found that high-anxious and defensive coping styles were associated with a six-fold higher risk for poststroke PTSD in comparison with low-anxious and repressive coping styles [ 48 ]. However, in the context of our finding that TIA patients reported an avoidance coping style, it must be considered that the phenomenon of avoiding feelings or thoughts can also be regarded as a cardinal symptom of PTSD, which indeed was demonstrated in 24.6% of the cases in the population we studied [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis in 2013 revealed the estimated rate of PTSD/PTSS following stroke or TIA was 23% within 1 year and 11% after 1 year (Edmondson et al, 2013b). Some more recent studies showed relatively lower rate: 7.5% within the first 5 days after ictus (Edmondson et al, 2013b), 10% (Pedowitz et al, 2021) or 11.0% at one month (Liyanage-Don et al, 2021), 12.9% at 3 months (Rutovic et al, 2021), 6.5% (Garton et al, 2020) or 11% (Assayag et al, 2022) at 12 months, although one reported as high as 32.8% at 3 months to 5 years follow-up (Dollenberg et al, 2021). The discrepancies between various studies may be partially explained by heterogeneity in study methodology (e.g., subtypes of stroke, first-ever or recurrent In our experience, the degree of cognitive impairment is also presumed to be a key reason.…”
Section: Epidemiology and Risk Factors Of Post-stroke Post-traumatic ...mentioning
confidence: 99%
“…It has been consistently shown that higher degree of stroke disability is positively correlated with both acute distress and PTSD symptoms (Garton et al, 2020;Pedowitz et al, 2021;Rutovic et al, 2021;Assayag et al, 2022). Other potential risk factors include lesions localized in the right cerebral hemisphere and brain stem (Rutovic et al, 2021), white matter damage (Assayag et al, 2022), minimally invasive surgery (Jiang, 2020), younger age, female sex, dysfunctional coping strategies, negative cognitive appraisals, lower education and unemployment status, uninsured status, etc. (Garton et al, 2017).…”
Section: Epidemiology and Risk Factors Of Post-stroke Post-traumatic ...mentioning
confidence: 99%
“…Due to sample heterogeneity, the prevalence of PTSD (or PTSD symptom) varies greatly, ranging from 4 to 37% [14]. Although some studies showed that the degree of disability caused by stroke correlates positively with PTSD symptoms [15][16][17][18], mild stroke [19] and TIA [20] can also lead to PTSD.…”
mentioning
confidence: 99%